Historical biogeography of amphibian parasites, genus Polystoma (Monogenea: Polystomatidae) - (:unkn) unknown (My University, 2006)
Aim The present-day geographical distribution of parasites with a direct biological life cycle is guided mostly by the past dispersal and vicariance events that have affected their hosts. The Amphibia–Polystoma association (which satisfies these criteria) also exhibits original traits, such as host specificity and world-wide distribution. This biological model was thus chosen to investigate the common historical biogeography of its widespread representatives. Location North and South America, Eurasia and Africa. Methods We investigated the phylogeny of 12 species of neobatrachian parasites sampled from North and South America, Eurasia and Africa. Hosts belonged mostly to hyloids and ranoids of families Bufonidae, Hylidae, Leptodactylidae, Ranidae and Hyperoliidae. Phylogenetic reconstructions were inferred from maximum likelihood and maximum parsimony analyses from complete ITS1 sequences. Results The group of American species appeared paraphyletic with one species at the base of a Eurafrican clade, within which two lineages were seen: one composed of only Eurasian species, and the other of European and African species, with the two European species basal to an African clade. Main conclusions The route of Polystoma evolution is deduced from the phylogenetic tree and discussed in the light of host evolution. We conclude that Polystoma originated in South America on hyloids, after the separation of South America from Africa. The genus must have colonized North America in Palaeocene times and Eurasia by the mid-Cainozoic, taking advantage of the dispersal of either ancestral bufonids or hylids. Africa, however, appears to have been colonized more recently, during the Messinian period.
Keywords: African Research